Study of Noni (Morinda citrifolia) Extract Addition to The Quality of Catfish (Pangasius hypopthalmus) By Smoked Fish During Storage - Ilhamdy, Aidil Fadli; Edison, Edison; Sumarto, Sumarto (Marinade, 2018)
The experiment was conducted from to May-June 2010. Research purposes were to determine the effect of noni extract to improve the storability of catfish (Pangasius hypopthalmus) smoked fish during storage. Noni extract concentration used 0 kg, 1 kg, 2 kg and 3 kg. While groups of storage 0 days, 7 days, 14 days, 21 days and 28 days. Parameters measured were an organoleptic score, peroxide value, analysis of water content and identification of fungi. The results, from the identification of fungi using the parameter of noni extract 3 kg can be maintained for 28 days, with high organoleptic value and the low moisture and peroxide values.